CHANGES IN THE FOREIGN TRADE OF ROMANIAN REGIONS – A SHIFT-SHARE ANALYSIS - Mihaela‐Nona CHILIAN; Marioara IORDAN (USV Annals of Economics and Public Administration, 2015)
The paper aims to assess the evolution of exports (overall and by sectors) in the regions of Romania. Considering the fact that the export base of a region acts more as an absolute advantage for the regional development, we use shift-share analysis tools to investigate the extent of the interregional trends and disparities in exports. The results reveal a diverse sectoral milieu and a trend towards higher diversification, better use of regional resources and technological upgrading, also providing useful insights for the general and specifically-targeted policy areas concerning regional development and business environment.